Impact of E-Service Quality on Customer Satisfaction and Loyalty Empirical Study in India Online Business - Vijayanand Sundaram; D Ramkumar; Poorna Shankar (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2017)
Due to Globalization and advancement in technology, Electronic commerce business (e-Com) has witnessed an extensive growth together with enthusiastic competition. The intention of this study is to test the conceptual framework of customer perception on service quality online business and its impact on satisfaction and loyalty through e-commerce business and a sample of 539 respondents were selected through simple random sampling method in Tamilnadu State of India. The result revealed that there is a significant association found between the demographic variables like Marital Status, Gender and Awareness about email/internet operation of the customers and the e-service quality, Customer Satisfaction and Loyalty except with Educational qualification and Status of the Residing area. The factors Responsiveness and Trust were highlighted as significant predictors for customer satisfaction and loyalty except Customization. Regarding the association between the customer satisfaction and loyalty, it is revealed that all the variables under satisfaction were significantly and positively associated with loyalty.Keywords: e-commerce, Retailers, Customer satisfaction, Customer Loyalty